Cerebral Venous Sinus Thrombosis Associated with Dutasteride Use - Choi, Bo Kyu; Cheon, Kyeongyeol; Cho, Bang-Hoon; Jung, Jae Wook; Lee, Kyung-Yul (Yonsei medical journal, 2020)
Cerebral venous thrombosis (CVT) is an uncommon cause of stroke that mainly affects young adults with known risk factors of prothrombotic conditions, pregnancy, infection, malignancy, and drugs. Dutasteride is a 5α-reductase inhibitor that is used for benign prostate hypertrophy and androgenetic alopecia. To date, CVT caused by dutasteride use has not been reported. A 25-year-old male presented with headache and diplopia. He had taken 0.5 mg of dutasteride every other day for 9 months to treat alopecia. A headache developed 7 months after he started taking medication, and horizontal diplopia occurred 1 month after the onset of headache. Fundus examination showed bilateral papilledema. Brain magnetic resonance imaging showed thrombosis in the left sigmoid and transverse sinuses. Headache and diplopia improved after discontinuing dutasteride and starting anticoagulation. The results from this case report indicated dutasteride as a potential cause of CVT. Presumably, the increased estrogen level due to dutasteride use caused the formation of a thrombus.